2014
DOI: 10.1101/gr.168872.113
|View full text |Cite
|
Sign up to set email alerts
|

Widespread contribution of transposable elements to the innovation of gene regulatory networks

Abstract: Transposable elements (TEs) have been shown to contain functional binding sites for certain transcription factors (TFs). However, the extent to which TEs contribute to the evolution of TF binding sites is not well known. We comprehensively mapped binding sites for 26 pairs of orthologous TFs in two pairs of human and mouse cell lines (representing two cell lineages), along with epigenomic profiles, including DNA methylation and six histone modifications. Overall, we found that 20% of binding sites were embedde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
460
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 435 publications
(513 citation statements)
references
References 69 publications
32
460
0
Order By: Relevance
“…A rapidly growing body of literature shows in different model systems Thompson et al 2016). Co-option of LTR sequences may have clear biological implications, as shown for human innate immunity (Chuong et al 2016), mammalian development (Chuong et al 2013;Lynch et al 2015;Nishihara et al 2016), evolution of mammalian gene regulatory networks (Xie et al 2010;Sundaram et al 2014), or RNA interference in mice (Flemr et al 2013). Our study represents a remarkable case of ERVL LTRs that function as gene-remodeling platforms that stochastically sculpt gene expression and function in oocytes and zygotes.…”
Section: Discussionmentioning
confidence: 83%
“…A rapidly growing body of literature shows in different model systems Thompson et al 2016). Co-option of LTR sequences may have clear biological implications, as shown for human innate immunity (Chuong et al 2016), mammalian development (Chuong et al 2013;Lynch et al 2015;Nishihara et al 2016), evolution of mammalian gene regulatory networks (Xie et al 2010;Sundaram et al 2014), or RNA interference in mice (Flemr et al 2013). Our study represents a remarkable case of ERVL LTRs that function as gene-remodeling platforms that stochastically sculpt gene expression and function in oocytes and zygotes.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, mobile genetic elements may themselves carry regulatory sequences and distribute these sequences in the genome as "plug-and-play" gene regulators (e.g., refs. 69,70). Although this model has not been proven for polymorphic Alu elements, it is supported for evolutionarily older elements that are fixed in the genome, including Alu elements that act as tissue-specific enhancers (e.g., refs.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have suggested a role for transposable elements (TEs) in the evolution of gene regulation, validating the functional contribution of TEs in mammalian gene regulation remains a challenge (McClintock 1950(McClintock , 1984Britten and Davidson 1969;Davidson and Britten 1979;Jordan et al 2003;Bejerano et al 2006;Wang et al 2007;Bourque et al 2008;Sasaki et al 2008;Markljung et al 2009;Kunarso et al 2010;Lynch et al 2011Lynch et al , 2015Schmidt et al 2012;Chuong et al 2013Chuong et al , 2016Jacques et al 2013;Xie et al 2013;del Rosario et al 2014;Sundaram et al 2014;Du et al 2016;Rayan et al 2016;Ward et al 2017).…”
mentioning
confidence: 99%